2022
DOI: 10.1088/2399-7532/ac4a86
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-binding peptides: understanding of selective binding and multifunctionality

Abstract: Platinum-binding peptides have been used for fabrication of complex platinum nanomaterials such as catalysts, metallopharmaceuticals, and electrodes. In this review, we present understanding of the mechanisms behind platinum-binding (Pt-binding) peptides and the applications of the peptides as multifunctional biomaterials. We discuss how the surface recognition, the roles of individual amino acids, and arrangement of amino acid sequences interplay. Our summary on the current state of understanding of Pt-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…99 There is an opportunity in the active Janus particle community to utilize polypeptide specificity for biological targets, as well as utilize polypeptide affinity for solid materials including gold 100 and platinum. 101 For example, peptide-functionalized gold nanoparticles already serve as effective cell-targeting agents. 102 In addition, peptides bound to solid surfaces have been shown to influence catalytic reactivity in various ways, including via controlling surface coverage and stabilizing catalyst composition (Figure 3).…”
Section: Affinity Sequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…99 There is an opportunity in the active Janus particle community to utilize polypeptide specificity for biological targets, as well as utilize polypeptide affinity for solid materials including gold 100 and platinum. 101 For example, peptide-functionalized gold nanoparticles already serve as effective cell-targeting agents. 102 In addition, peptides bound to solid surfaces have been shown to influence catalytic reactivity in various ways, including via controlling surface coverage and stabilizing catalyst composition (Figure 3).…”
Section: Affinity Sequencesmentioning
confidence: 99%
“…105 Examples of controlling platinum reactivity via peptides have also been reported. 101 Affinity is assessed using techniques such as isothermal calorimetry, surface plasmon resonance, and quartz crystal microbalance with dissipation monitoring.…”
Section: Affinity Sequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Technology which enables the use of peptides on polymer scaffolds would be useful for REE capture as well as: phosphate capture, 29 antimicrobial coatings, 31 copper and zinc capture, 32 and precious metal capture. 33 Current state-of-the-art technology for bio-inspired REE recovery focuses on column separations using whole lanmodulin protein 34 – while this strategy may be effective, peptides can potentially be attached at higher densities on a separation material due to their smaller size (∼1600 Da for peptide, ∼12 000 Da for lanmodulin 35 ). Our previous study demonstrated the ability of gold-bound peptide to capture REEs, 29 however a gold surface likely has limited applications.…”
Section: Introductionmentioning
confidence: 99%